2012
DOI: 10.5301/ru.2012.9392
|View full text |Cite
|
Sign up to set email alerts
|

Role of SOCS3 Evaluated by Immunohistochemical Analysis in a Cohort of Patients Affected by Prostate Cancer: Preliminary Results

Abstract: SOCS3- pt turned out to have a more aggressive disease compared with SOCS3+. In particular, also SOCS3+/- patients seemed to have an aggressive behavior. The non-expression of SOCS3 protein may identify PC with more aggressive behavior and can be evaluated with immunohystochemical analysis, which is a relatively easy and cheap procedure in clinical practice. These results, if confirmed by a wider population and a longer follow-up, may encourage the research on the use of this molecular family as a prognostic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…For the IHC studies, the avidin‐biotin‐peroxidase complex method was performed on paraffin sections applying technical procedures previous reported and using a commercially available kit (Dako LSAB2, Dakopatts, Glostrup, Denmark) and the following commercially available monoclonal antibodies: CK20 (1:200, DAKO, Carpinteria, CA), CD44 (1:640 Pharmingen San Diego CA, p53 (1:200, BioGenex, San Ramon, CA and Ki‐67 (MIB‐1; 1:200, DAKO, Carpinteria, CA), p53 (1:200, BioGenex, San Ramon, CA), and CK20 (1:200, DAKO, Carpinteria, CA).…”
Section: Methodsmentioning
confidence: 99%
“…For the IHC studies, the avidin‐biotin‐peroxidase complex method was performed on paraffin sections applying technical procedures previous reported and using a commercially available kit (Dako LSAB2, Dakopatts, Glostrup, Denmark) and the following commercially available monoclonal antibodies: CK20 (1:200, DAKO, Carpinteria, CA), CD44 (1:640 Pharmingen San Diego CA, p53 (1:200, BioGenex, San Ramon, CA and Ki‐67 (MIB‐1; 1:200, DAKO, Carpinteria, CA), p53 (1:200, BioGenex, San Ramon, CA), and CK20 (1:200, DAKO, Carpinteria, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Elevated levels of the IL-6 cytokine have been found repeatedly in both serum and local tissue samples taken from prostate cancer patients,(52, 53) and suppression of SOCS3 via expression of IL-6 has been implicated in the development(54) and aggressiveness(55) of prostate cancer. These findings may point to an important causal factor for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, SOCS‐3 is expressed in PCa tissue samples and SOCS‐3 expression increases during the progression of carcinoma. However, other reports have indicated that negative SOCS‐3 staining is correlated with an aggressive tumor behavior . Therefore, SOCS‐3 may have a role as a tumor diagnostic and prognostic marker; further studies are needed to verify this hypothesis using larger sample sizes.…”
Section: Potential Clinical Applications Of Socs‐3 In Pcamentioning
confidence: 91%
“…They concluded that patients lacking SOCS‐3 had a more aggressive disease than patients expressing SOCS‐3 in cancer tissues. Moreover, patients with partial expression of SOCS‐3 also exhibited a more aggressive disease …”
Section: The Multiple Function Of Socs‐3 In Pcamentioning
confidence: 99%